Type 2 immunity in intestinal homeostasis and inflammatory bowel disease. (1st November 2021) - Luo, Xinxin; Villablanca, Eduardo J.
Abstract : Type 2 immune responses commonly emerge during allergic reactions or infections with helminth parasites. Most of the cytokines associated with type 2 immune responses are IL-4, IL-5, and IL13, which are mainly produced by T helper 2 cells (TH 2), eosinophils, basophils, mast cells, and group 2 innate lymphoid cells (ILC2s). Over the course of evolution, humans have developed type 2 immune responses to fight infections and to protect tissues from the potential collateral damage caused by inflammation. For example, worm parasites induce potent type 2 immune responses, which are needed to simultaneously clear the pathogen and to promote tissue repair following injury. Due to the strong type 2 immune responses induced by helminths, which can promote tissue repair in the damaged epithelium, their use has been suggested as a possible treatment for inflammatory bowel disease (IBD); however, the role of type 2 immune responses in the initiation and progression of IBD is not fully understood. In this review, we discuss the molecular and cellular mechanisms that regulate type 2 immune responses during intestinal homeostasis, and we briefly discuss the scarce evidence linking type 2 immune responses with the aetiology of IBD.